STRATEGI GURU DALAM MENANAMKAN SIKAP DISIPLIN SISWA PADA PROSES PEMBELAJARAN DI KELAS IV SDN HARAPAN BARU II - Aprilya, Deka; Yohamintin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
As the main component in the learning process, teachers play an important role. The role of teachers is to educate, teach, guide and train and motivate students, so that they are able to be disciplined, in order to succeed in pursuing education. Teachers have a big role in educating students because teachers can train students' discipline at school so that good character is formed in children. The purpose of this study was to determine the extent of the teacher's strategy in instilling a disciplined attitude in the learning process at SDN Harapan Baru II Bekasi. This study uses a qualitative method with a descriptive research type. Data collection techniques in this study were carried out by observation, interviews and documentation to teachers at SDN Harapan Baru II Bekasi. The results of this study indicate that the teacher's strategy in instilling a disciplined attitude is good because with teachers being disciplined examples for students, the teachers there have displayed and provided examples of good attitudes in implementing the character of student discipline.